MANAJEMEN POTENSI EKONOMI TUNA MATA BESAR (Thunnus obesus) YANG DIDARATKAN DI PELABUHAN BENOA, BALI - I Putu Gede Eka Handrayana Putra; Suprabadevi Ayumayasari Saraswati; Sunzexcri Apri Seven Hutagalung; Revalina Najwa Sunarya; Khofifah Salsabilah; Angel Eka Laurentsia (Jurnal Sosial Terapan, 2025)
Bigeye tuna (Thunnus obesus) is an economically important commodity landed at Benoa Port, yet it currently faces challenges regarding declining catch efficiency and economic value. This study aims to analyze Catch per Unit Effort (CPUE) trends, estimate Maximum Sustainable Yield (MSY), and examine the dynamics of economic production value to determine appropriate management strategies. The research employed a survey method utilizing operational landing time-series data from 2020 to 2024. Data were analyzed using the Gordon-Schaefer model. The results indicated that a surge in fishing effort in 2024, reaching 456 trips, was not commensurate with the catch, causing the CPUE to drop significantly to its lowest value of 2.16 tons/trip. The MSY was estimated at 1,272.12 tons/year with an optimum fishing effort of 489.41 trips/year. Although the resource utilization rate remains in the Moderate Exploited category (77.3%), the fishing effort level has approached a critical point, reaching 93.2% of the optimum limit. Economically, there was a significant decline in production value from IDR 58.1 billion in 2020 to IDR 19.6 billion in 2024, attributed to falling prices and smaller fish sizes. It is concluded that tuna fisheries management in Benoa requires the immediate implementation of fishing effort restrictions and an orientation towards improving catch quality to prevent overfishing and restore economic profitability.